KETAHANAN PANGAN DALAM BAYANG-BAYANG PERUBAHAN IKLIM DENGAN TINJAUAN MENGENAI MITIGASI DAN ADAPTASI MELALUI HUKUM - Bentar Zamzami Firmansyah (ABISATYA DINAMIKA ISWARA, 2024)
This research discusses the issue of food security in the shadow of climate change by looking at it from the perspective of mitigation and adaptation through law. Drastic and erratic climate change has had a negative impact on food production and availability. This literature study shows how adaptation and mitigation through law is an important key to dealing with this issue. Through analysis of legal documents, policies and related literature, this research explores how law can be an effective instrument in facilitating mitigation and adaptation to climate change to ensure food security. Laws should be seen as important tools for promoting clean and sustainable technologies, agricultural practices and the sustainable use of natural resources. In addition, this research also reflects the need for synergy between law, policy and concrete action in order to ensure food security.